1997
DOI: 10.2527/1997.75114x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of rambouillet sheep expressing the callipyge gene: I. Inheritance of the condition and production characteristics.

Abstract: The objectives of this study were to determine the model of inheritance of the callipyge gene and to evaluate the growth, ADFI, feed efficiency, reproductive performance, and wool growth of sheep that are heterozygous for the callipyge gene. Ewes (n = 236) with a normal muscle phenotype and genotype were mated to three heterozygous rams that expressed the callipyge gene. Lambs (n = 311) were subjectively classified at weaning (90 to 120d) according to muscle phenotype by a panel of three evaluators working ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
2
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 11 publications
7
76
2
3
Order By: Relevance
“…These results are consistent with those of Jackson et al (1997a), who report that no differences were detected between callipyge phenotypes for birth weight, weaning weight, and postweaning daily gain. However, compositional targets for callipyge sheep can be achieved at greater live and carcass weights.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are consistent with those of Jackson et al (1997a), who report that no differences were detected between callipyge phenotypes for birth weight, weaning weight, and postweaning daily gain. However, compositional targets for callipyge sheep can be achieved at greater live and carcass weights.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, the lighter weight of internal organs is consistent with the reduced daily feed intake of callipyge compared with normal lambs (Jackson et al, 1997a). Jackson et al (1997a) reported that callipyge phenotype decreased 12-mo fleece weights of yearling Rambouillet ewes by approximately 18%. These researchers hypothesized that dietary amino acids were preferentially converted to lean tissue growth rather than to wool growth.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These superior carcass traits translate into improved yields of wholesale leg, loin, rack, and shoulder from callipyge animals by 11.8%, 4.7%, 2.5%, and 2.3%, respectively, over normally muscled lambs [9]. In addition, callipyge lambs exhibit superior feed efficiencies and lower daily feed intakes [24], which result in lower production expenses. Therefore, the widespread production of callipyge lamb would have the potential to lower the cost of lamb for consumers and to increase the profitability of the sheep industry.…”
Section: The Callipyge (Clpg) Locusmentioning
confidence: 99%
“…In an extensive survey of 19 muscles dissected from the right side of carcasses from normal and callipyge individuals [26], the total weight of excised muscles from the pelvic, torso, and thoracic limbs was greater in callipyge lambs by 42%, 50%, and 14%, respectively, than in normally muscled half-sibs. This muscle hypertrophy develops after about three weeks of age [24], so there is no increased risk of dystocia for callipyge lambs.…”
Section: The Callipyge (Clpg) Locusmentioning
confidence: 99%